The State of Healthcare Facilities in the Field of Cardiovascular Diseases: Reflections from a Public Cardiac Hospital, Uttar Pradesh - Singh, Arti (Indian Journal of Community Health, 2020)
Background: Literature suggest that majority of Indians belonging to lower socio-economic status (SES) are dependent on public health sector but still there is higher rate of deaths among them due to cardiac diseases. Objective: The aims of this paper are twofold: (i) To depict the ground realities of a public cardiac hospital, and (ii) To identify the key challenges for the effective policy implementation and control of CVD. Method: Using direct field based observation, experiences and field notes. Result and Conclusion: India’s public healthcare sector for cardiac patients suffers from problem of accessibility and affordability. Further, prevalence of prohibited practices makes things worse for the poor patients.